Constantine and the bishops the politics of intolerance - Drake, H. A. 1942- (Johns Hopkins Univ. Press, 2000)
Historians who viewed imperial Rome in terms of a conflict between pagans and Christians have often regarded Constantine's conversion as the triumph of Christianity over paganism. Here Drake offers a fresh understanding of Constantine's rule.
Keywords: Athanase <saint, patriarche d'Alexandrie, ca 293-373>; Athanasius <Saint, Patriarch of Alexandria, d. 373> - Relations with Constantine I; Constantin <I, empereur de Rome, m. 337> - Religion; Constantine <I, Emperor of Rome> - Religion; Athanasius <Saint, Patriarch of Alexandria, d. 373>; Constantine <I, Emperor of Rome, d. 337> -- Religion; Konstantin -- I. -- Römisches Reich, Kaiser -- ca. 280-337; Bisschoppen; Intolérance - Rome; Keizers; Kirchengeschichte; Machtsstrijd; Paganisme - Rome; Politik; Religion et État - Rome; Église - Histoire - ca 30-600 (Église primitive) - Aspect politique; Church history -- Primitive and early church, ca. 30-600 -- Political aspects; Paganism -- Rome; Religion and state -- Rome; Toleration -- Rome; Christentum; Rom